2010
DOI: 10.1186/1471-2164-11-8
|View full text |Cite
|
Sign up to set email alerts
|

Detecting positive selection from genome scans of linkage disequilibrium

Abstract: BackgroundThough a variety of linkage disequilibrium tests have recently been introduced to measure the signal of recent positive selection, the statistical properties of the various methods have not been directly compared. While most applications of these tests have suggested that positive selection has played an important role in recent human history, the results of these tests have varied dramatically.ResultsHere, we evaluate the performance of three statistics designed to detect incomplete selective sweeps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 25 publications
3
25
0
Order By: Relevance
“…Tests based on extreme differences in allele frequencies are useful for identifying single-site differences between populations, in contrast to within-population, haplotype-based sweeps that may be present and strongly detectable at intermediate allele frequencies (Voight et al 2006;Huff et al 2010). One example is the PPARA haplotype, which exhibits a significant iHS signal and is correlated with hemoglobin concentration in the Qinghai-Tibetan population (Simonson et al 2010) but has not been reported as a selection candidate in other studies.…”
Section: Shared and Unique Gene Targets And Associations Identified Imentioning
confidence: 96%
See 1 more Smart Citation
“…Tests based on extreme differences in allele frequencies are useful for identifying single-site differences between populations, in contrast to within-population, haplotype-based sweeps that may be present and strongly detectable at intermediate allele frequencies (Voight et al 2006;Huff et al 2010). One example is the PPARA haplotype, which exhibits a significant iHS signal and is correlated with hemoglobin concentration in the Qinghai-Tibetan population (Simonson et al 2010) but has not been reported as a selection candidate in other studies.…”
Section: Shared and Unique Gene Targets And Associations Identified Imentioning
confidence: 96%
“…Haplotype tests of selection, for example, are based on patterns of extended homozygosity across a genomic region rather than differences in allele frequency. The within-population integrated haplotype score [iHS (Voight et al 2006)], which was used by Simonson et al (2010) to determine EGLN1/ PHD2 and PPARA haplotype SNPs, has the greatest power to identify selective sweeps when the selected variant is present at intermediate (20-80%) frequency in a single population (Voight et al 2006;Huff et al 2010). Extreme allele frequency differences are, therefore, not necessarily expected to be observed among a subset of SNPs used to tag a region that exhibits an intermediate selective sweep signal.…”
Section: Shared and Unique Gene Targets And Associations Identified Imentioning
confidence: 99%
“…However, functional mutations (SNPs) that have occurred relatively recently in human history have much longer chunks of unchanged DNA surrounding them. Several new statistical tests have been developed to evaluate the presence of selective sweeps and their population frequency (Huff, Harpending, & Rogers, 2010;Pickrell et al, 2009;Sabeti et al, 2002;Voight, Kudaravalli, Wen, & Pritchard, 2006). These tests are particularly effective at identifying selective sweeps at moderate frequency (~50%-80%), and at high frequency (>80% to fixation) within a population (Pickrell et al, 2009).…”
Section: Environment Influences the Genetic Structures Of Human Groupmentioning
confidence: 99%
“…Some generic LIMS target specific laboratory tasks, such as sample management3910, laboratory work-flows and protocols2111213, documentation, management of lab stocks, or clinical studies14. Further solutions exist for molecular genetics and the creation of vector libraries15.…”
mentioning
confidence: 99%